A chromosome‐level genome assembly enables the identification of the follicule stimulating hormone receptor as the master sex‐determining gene in the flatfish Solea senegalensis. (15th January 2023) - de la Herrán, Roberto; Hermida, Miguel; Rubiolo, Juan Andres; Gómez‐Garrido, Jèssica; Cruz, Fernando; Robles, Francisca; Navajas‐Pérez, Rafael; Blanco, Andres; Villamayor, Paula Rodriguez; Torres, Dorinda; Sánchez‐Quinteiro, Pablo; Ramirez, Daniel; et al.
Abstract: Sex determination (SD) shows huge variation among fish and a high evolutionary rate, as illustrated by the Pleuronectiformes (flatfishes). This order is characterized by its adaptation to demersal life, compact genomes and diversity of SD mechanisms. Here, we assembled the Solea senegalensis genome, a flatfish of great commercial value, into 82 contigs (614 Mb) combining long‐ and short‐read sequencing, which were next scaffolded using a highly dense genetic map (28, 838 markers, 21 linkage groups), representing 98.9% of the assembly. Further, we established the correspondence between the assembly and the 21 chromosomes by using BAC‐FISH. Whole genome resequencing of six males and six females enabled the identification of 41 single nucleotide polymorphism variants in the follicle stimulating hormone receptor ( fshr ) consistent with an XX/XY SD system. The observed sex association was validated in a broader independent sample, providing a novel molecular sexing tool. The fshr gene displayed differential expression between male and female gonads from 86 days post‐fertilization, when the gonad is still an undifferentiated primordium, concomitant with the activation of amh and cyp19a1a, testis and ovary marker genes, respectively, in males and females. The Y‐linked fshr allele, which included 24 nonsynonymous variants and showed a highly divergent 3D protein structure, was overexpressed in males compared to the X‐linked allele at all stages of gonadal differentiation. We hypothesize a mechanism hampering the action of the follicle stimulating hormone driving the undifferentiated gonad toward testis.